Thioredoxin Is Involved in Oxygen-Regulated Formation of the Photosynthetic Apparatus of Rhodobacter sphaeroides - Pasternak, Cecile (American Society for Microbiology (ASM), 1999)
Thioredoxin, a redox active protein, has been previously demonstrated to be essential for growth of the anoxygenic photosynthetic bacterium Rhodobacter sphaeroides. In the present study, the involvement of thioredoxin in the formation of the photosynthetic apparatus of R. sphaeroides WS8 was investigated by construction and analysis of a mutant strain disrupted for the chromosomal trxA copy and carrying a plasmid-borne copy of trxA under the control of the hybrid p(trc) promoter inducible by IPTG (isopropyl-β-d-thiogalactopyranoside). This strain was viable in the absence of IPTG but was affected in pigmentation. When shifted from high to low oxygen tension conditions, the trxA mutant showed a reduced bacteriochlorophyll content in comparison to that of the wild type. Although thioredoxin is able to regulate aminolevulinic acid (ALA) synthase (the first enzyme of the tetrapyrrole biosynthetic pathway) activity by a dithiol-disulfide exchange, our mutant strain exhibited a level of ALA synthase activity identical to that of the wild type, suggesting that thioredoxin is involved in other steps to regulate the synthesis of the photosynthetic apparatus. Accordingly, we showed that the trxA mutation affects the oxygen-regulated expression of the puf operon encoding the pigment-binding proteins of the light-harvesting and reaction center complexes. Upon transition from aerobic to semiaerobic growth conditions, the maximal puf mRNA level was found to be 40 to 50% lower in the mutant strain than in the wild type. The stability of the puf transcripts was identical in both strains grown under low oxygen tension, indicating that the role of thioredoxin in regulating puf expression occurs at the transcriptional level.